Penerapan Model Discovery Learning Berbantuan Alat Peraga Sederhana untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas VII SMPN 5 Jonggat Tahun Pelajaran 2015/2016 - Ida Suprayanti; Syahrial Ayub; Satutik Rahayu (Department of Physics Education, Universitas Mataram, 2016)
This research is a classroom action research (PTK) which aims to increase physical activity and learning outcomes of students of class VII SMPN 5 Jonggat in academic year 2015/2016 by applying the model-aided Discovery Learning with simple props. Classroom action research consists of four stages, that are planning, implementation, observation, and reflection, while the implementation of the model of Discovery Learning aided with simple props was done through six stages, that are stimulation, problem identification, datacollectingby using props simple, data processing, verification and conclusion. This research was done in two cycles. Based on the result of research that had been done, obtained theaverage score of student learning activities in first cycle in the first and second meeting were 8.8 in sufficient active category and 12 in the active category. The evaluation results in first cycle obtained average grade reaches 60 with classical completeness 73%. In second cycle,the average score of student learning activity in the first and second meeting were 16.6 and 18, with both of them are in the very active category. The average results of students in the second cycle increased to 68 and 85% of classical completeness. Based on the results of the research, it could be concluded that the application of the model-aided Discovery Learning with simple props can increase the activity and learning result of students of class VII SMPN 5 Jonggat in academic year 2015/2016.